Graphene and Polymer Nanoparticle Electrocatalysis - Chen, L (2019)
This thesis reports experimental work with two main aims: the first is the detection and characterisation of single graphene and polymer nanoparticles with an emphasis on their electrocatalysis; the second is to develop a more comprehensive understanding of nanoscale interfacial reactions kinetically and mechanistically.